Correction: Photoinduced electron transfer of poly(o-phenylenediamine)–rhodamine B copolymer dots: application in ultrasensitive detection of nitrite in vitro. Issue 3 (16th December 2016) - Liao, Fang; Song, Xun; Yang, Siwei; Hu, Chenyao; He, Lin; Yan, Shuai; Ding, Guqiao
Abstract : Correction for 'Photoinduced electron transfer of poly( o -phenylenediamine)–rhodamine B copolymer dots: application in ultrasensitive detection of nitrite in vivo ' by Fang Liao et al., J. Mater. Chem. A, 2015, 3, 7568–7574.